Answer:
-
![3x^(2)](https://img.qammunity.org/2021/formulas/mathematics/college/bko05wj7cedjwkg79ok61nq0hbamoi9oq4.png)
Explanation:
-x= -1x. (The 1 is invisible)
Now lets do the 3*-1= -3
You still have both of the x's.
All you do is add them. 1+1=2
So, your exponent is going to be 2 with x attached
***When you are multiplying and you have the same exponent, add them. Pretend that you see the exponent 1 by the x (
) now since you have 2 (
) which equals (
)
Looks Like:
3x* -x
=3x* -(1)x
=
![-3x^(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/97y8l8csuctcnc6t7uumls0u3bk9uwft7f.png)
Hope this helped :)